Perlunya Tentara Nasional Indonesia Memiliki Angkatan Siber Guna Menghadapi Era Cyber warfare - Krida Eva Setyawan Hasan (Mahesa Research Center, 2022)
This article aims to identify and explain the need for the Indonesian National Armed Forces (TNI) to form a cyber force, given the increasingly rapid development of technology. The problem in this article is focused on the threat of cyber crime, especially for state sovereignty and the emphasis that at this time Indonesia needs the Indonesian National Armed Forces (TNI) for cyber forces to protect and eradicate cyber crime in Indonesia. This article uses the literature study method by taking references from various trusted sources and related articles. The results of the study show that currently cyber war is in sight, in the sense that every country must be prepared for this. For example, espionage carried out by other countries against Indonesia certainly threatens Indonesia's security. Therefore, it is necessary to establish a fourth dimension, namely the cyber army or the Cyber Force TNI for the creation of maximum and equitable national defense and security. As with various countries that already have a special military force for cyber, Indonesia must also immediately realize it.